Early treatment of vulvar synechiae in childhood - prevention of late complications - Janštová, Alena; Nováčková, Marta (Ceska gynekologie, 2023)
Synechiae of the vulva occurs especially in girls in the so-called resting hormonal period with a minimal serum concentration of estrogens. If the external genitalia of the girl are not treated properly, the mucous membrane of the vaginal entrance is not regularly checked and mechanically removed, then the smegma of the opposite mucous membranes of the vulva can stick together. The place of the adhesion of epithelium in the vaginal introitus can be covered by a new epithelium and can create a firm adhesion, synechiae of the vulva, which is usually asymptomatic and is discovered incidentally during pediatric examination. Clinically significant vulvar synechiae can cause impaired bladder evacuation and recurrent lower urinary tract infections. Dissection of synechiae in the stage of conglutination or thin adhesion is performed manually on an outpatient basis, but extensive and firm adhesions must be divided surgically under general anesthesia. Local application of cream with estriol or betamethasone is also used for the therapy of synechiae of the vulva, but this treatment is more time-consuming compared to rapid manual separation and requires good compliance of the girls and their parents. The prevention of synechiae is based on the education of parents by pediatricians and gynecologists about the need for regular checks of the external genitalia and sufficient hygiene.
Keywords: Female; conservative therapy; dítě; Tissue Adhesions; ženské pohlaví; Vagina; lidé; Vulva; manual separation; estrogeny; Vulvar Diseases; adheze tkání; Estrogens; vulvovaginitis; conservative treatment; nemoci vulvy; Child; synechiae of the vulva; conglutination vulvae infantum; vulva; vagina; Humans